2017
DOI: 10.1049/iet-nbt.2016.0254
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the CuO nanoparticles using Euphorbia Chamaesyce leaf extract and investigation of their catalytic activity for the reduction of 4‐nitrophenol

Abstract: Through this study an eco-friendly, simple, efficient, cheap and biocompatible approach to the biosynthesis and stabilisation of CuO nanoparticles (NPs) using the Euphorbia Chamaesyce leaf extract is presented. The CuO NPs were monitored and characterised by field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transformed infrared spectroscopy, transmission electron microscope and UV-visible spectroscopy. The biosynthesised CuO NPs showed good catalytic activity for the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The peaks at 622 cm −1 and around 1010–1122 cm −1 in S 2 and S 3 illustrate the stretching of O–Mn–O lattice vibrations [1, 38]. The wideband at 3000–3600 cm −1 assigned to the –OH band [39, 40]. The FTIR spectra confirm the presence of metal oxide NPs in the S 1 , S 2 , and S 3 .…”
Section: Resultsmentioning
confidence: 87%
“…The peaks at 622 cm −1 and around 1010–1122 cm −1 in S 2 and S 3 illustrate the stretching of O–Mn–O lattice vibrations [1, 38]. The wideband at 3000–3600 cm −1 assigned to the –OH band [39, 40]. The FTIR spectra confirm the presence of metal oxide NPs in the S 1 , S 2 , and S 3 .…”
Section: Resultsmentioning
confidence: 87%
“…The copper and copper oxide nanoparticles were found to possess spherical shapes with an average size of 53 nm ( Table S10 ). Numerous researchers conducted FTIR characterization techniques on the extract solutions and nanostructures which found that the reduction in the metallic ions resulted from phytochemicals such as phenols, flavones, terpenoids, proteins, and other heterocyclic compounds present during the reaction [ 78 , 79 , 80 , 81 ]. Copper-based nanomaterial studies also indicated initial aggregation of the particles that increased over time [ 82 , 83 ].…”
Section: Green Synthesis Of Transitional Metals and Their Oxidesmentioning
confidence: 99%
“…Catalysis has been explored and reported in the literature as a crucial and potentially useful topic for the efficient usage of biosynthetic CuO NPs [50]. For instance, Maham et al effectively manufactured CuO NPs using Euphorbi chamaesyce leaf extract and studied their catalytic reduction of 4-nitrophenol [51]. They discovered that within 180 s, CuO NPs could achieve 100% 4-nitrophenol removal.…”
Section: Introductionmentioning
confidence: 99%